Use of polyamide tie-rap for ovariectomy in standing mares - Rabelo, Rogério Elias; Silva, Luiz Antônio Frando da; Sant’Ana, Fabiano José Fereira de; Silva, Marco Augusto Machado; Moura, Maria Ivete; Franco, Leandro Guimarães; Lima, Caroline Rocha de Oliveira (Acta Scientiae Veterinariae, 2018)
Ovariectomy is a common surgical spaying method in mares, which it leads to short/medium-term masculinization and improves especially their stamina. This study aimed to assess the economic, clinical and histological aspects of the polyamide tie-rap for haemostasis in surgical sterilization of twelve seven-year-old mares, with or without ovary excision. The equines were spayed with polyamide tie-rap for pedicle preventive haemostasis. The left ovary was excised after mesovarium clamping. The polyamide device was also used in the opposite pedicle, though the ovary was not excised. The mean operating cost was determined, the wound healing was assessed and macroscopic and histological evaluation of the pedicles and ovaries were achieved in the post-op. The mean operating cost of the surgical procedure was US 69,44. The ovaries were atrophied and with multifocal necrosis areas, firm irregular nodules and follicles. These nodules were histologically recognized as granulomas. The polyamide tie-rap was efficient in controlling hemorrhage and safe for surgical purpose in the experimental model studied. However, it did not interrupt ovarian activity in the non-excised gland.